IEO Annual Report 2009. - International Monetary Fund. Independent Evaluation Office (Washington, D.C. : International Monetary Fund, 2009)
This sixth Annual Report describes the activities of the Independent Evaluation Office (IEO) during the year to April 30, 2009. The report summarized the findings of IEO's most recent evaluations, lists cross-cutting lessons highlighted in previous years' reports, and discusses ongoing evaluation projects. The report also describes the new framework for monitoring and following up on the implementation of IEO recommendations approved by the IMF Executive Board.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet